Molecular Characterization and Prognostication of Large Cell Neuroendocrine Carcinoma and Large Cell Carcinoma - Chen, Ying; Cui, Xiaoying; Wang, Di; Xia, Guojie; Xing, Minyan; Cheng, Lei; Sheng, Liming; Du, Xianghui (Frontiers in Oncology, 2022)
Purpose: Large cell neuroendocrine carcinoma (LCNEC) and classic large cell carcinoma (LCC) are two distinct entities with different histological and biological characteristics. However, the mutational profiles and the clinical behavior of the two subtypes of lung cancer remain to be explored. Patients and methods: Pathological diagnoses of all screened patients were finally confirmed by three or four experienced pathologists. Patients with uncertain pathological diagnoses were excluded. Finally, we genetically profiled ten patients with LCNEC and seven with LCC. ALL patients patients were subjected to next-generation sequencing (NGS) test, which included nine patients sequenced with a 139-gene panel and eight patients with a 425-gene panel. Including only intersected mutations from these two panels, survival analysis was further conducted. Results: Both LCNEC and LCC showed high prevalence in male patients, with no clear association with smoking history. Potential targetable mutations in KRAS and RET were detected in the study cohort. However, LCNEC and LCC showed distinct mutational profiles with an enrichment of RB1/TP53 co-mutations in a subset of LCNEC patients. SMARCA4 and KEAP1 mutations were exclusively found in LCC patients, and RICTOR, BRAF, ROS1 and TET2 mutations were only detected in LCNEC. LCC patients in the cohort had shorter survival compared to LCNEC patients (p=0.006). Survival analysis revealed an association between SMARCA4 mutations and poor outcome in the study cohort and in the LCC subset. Mutations in BRAF were associated with a trend of increased survival in the study cohort, as well as in the LCNEC subset. Finally, TET2 mutations were associated with poor outcome in the LCNEC cohort. Conclusion: LCC and LCNEC were both heterogeneous diseases with limited treatment options. Out study identified potential targetable mutations and prognostic biomarkers that might provide more therapeutic options and improve individualized patient care.